Ответ:
(a+1)²+3(а-1)2-5(a+1)(а-1)=
1) (a+1)2=(a+1)(a+1)=a2+a+a+1=a2+2a+1 2) 3(а-1)2=3(а-1)(a-1)=3(a²-a-a+1)=3a3-6a+3 3) 5(a+1)(a-1)=(5a+5) (a-1)=5a2-5a+5a-5=5a²-5
=(a2+2a+1)+(3a2-6a+3)-(5a²-5)=a2+2a+1+3a2-6 a+3-5a2+5=-a2-4а+9
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
(a+1)²+3(а-1)2-5(a+1)(а-1)=
1) (a+1)2=(a+1)(a+1)=a2+a+a+1=a2+2a+1 2) 3(а-1)2=3(а-1)(a-1)=3(a²-a-a+1)=3a3-6a+3 3) 5(a+1)(a-1)=(5a+5) (a-1)=5a2-5a+5a-5=5a²-5
=(a2+2a+1)+(3a2-6a+3)-(5a²-5)=a2+2a+1+3a2-6 a+3-5a2+5=-a2-4а+9